New application of dynamic magnetic resonance imaging for the assessment of deglutitive tongue movement - Issareeya Ekprachayakoon; Jun J. Miyamoto; Maristela Sayuri Inoue-Arai; Ei-ichi Honda; Jun-ichi Takada; Tohru Kurabayashi; Keiji Moriyama (Progress in Orthodontics, 2018)
Abstract Background Deglutitive motion of the tongue may function to maintain tooth position. However, the causation between abnormal patterns of orofacial muscle function and dental malocclusion remains unclear. To clarify the pathogenic mechanism of malocclusion, it is important to determine the relative positional relationship between the tongue tip and incisor edge or the dorsal tongue and palate during deglutition. Here, we assessed the utility of 3-T segmented cine-magnetic resonance (MR) imaging, combined with static MR images for hard tissue visualization, in assessing the relationship between the tongue and the surrounding tissues during deglutitive tongue movement. Methods Cine-MR images were acquired from three healthy female volunteers during deglutition who had no history of swallowing disorder or other chronic illness, normal alignment and occlusion, and a skeletal class I relationship. Three cine-MR images were taken during deglutition in accordance with an auditory cue for each volunteer. During static imaging, custom-made, contrast-medium-filled clear retainers were positioned in the mouth to allow visualization of the upper and lower incisors and hard palate boundaries. Static images were superimposed onto images of the three stages in deglutitive tongue movement, which were selected from a series of cine-MR images. These superimpositions were assessed five times by tracing cephalometric parameters to examine the reproducibility of the method. Results Traces varied little across repeated measurements, and all subjects had a similar pattern of dorsal tongue movement. Tongue-to-palate contact increased slightly during the first to second stage of swallowing and abruptly increased during the second to third stage, while the tongue tip position remained constant. Conclusions Segmented cine-MR imaging combined with static MR images is useful for assessing soft tissue motion during deglutition. This method is particularly useful in dentistry to evaluate the relationship between tongue function and maxillofacial morphology in terms of orthodontic treatment and orofacial myofunctional therapy, and for improving tongue movement during speech therapy.